Titanium-aluminum-nickel high-temperature alloy and preparation method thereof

By adding trace elements such as C and Ce to TiAl alloy and optimizing process conditions to form a titanium-aluminum-nickel high-temperature alloy with a layered structure, the existing TiAl alloys are solved inadequate compressive strength and creep resistance under high temperature conditions. The problem is to achieve both high-temperature performance and processability.

CN118685661BActive Publication Date: 2025-02-07ZHEJIANG METALLURGICAL RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410784529.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-02-07
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

The existing β-phase stable TiAl alloys sacrifice high-temperature performance when improving processability, making it difficult to maintain compressive strength and creep resistance under high temperature conditions.

Method used

By simultaneously adding trace elements C and Ce to the TiAl alloy and optimizing the element ratio and process conditions, a titanium aluminum-nickel high-temperature alloy with a layered structure is formed, including a phase a, γ phase, β phase and Ti3AlC particles, and β phase volume fractions. Controlled at 5-18%.

Benefits of technology

It achieves improvements in high-temperature compressive strength and creep resistance, while maintaining excellent processability and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118685661B_ABST
    Figure CN118685661B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of high-temperature alloys, and discloses a titanium-aluminum-nickel high-temperature alloy and a preparation method thereof. The titanium-aluminum-nickel high-temperature alloy comprises the following chemical components: Al=45-50%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4% and the balance Ti. The present invention simultaneously adds trace elements such as C and Ce to the TiAl alloy and optimizes the element ratio, while combining process optimization to obtain a titanium-aluminum-nickel high-temperature alloy having excellent high-temperature compressive strength and creep resistance, as well as excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high temperature alloys, and in particular to a titanium-aluminum-nickel high temperature alloy and a preparation method thereof. Background Art

[0002] TiAl alloys have the characteristics of low density, high strength and high oxidation resistance, which makes them excellent candidates for high temperature applications. With the improvement of alloy chemistry and microstructure, TiAl alloys have been used in the automotive and aerospace engine industries. However, the disadvantage of TiAl alloys is poor machinability.

[0003] At present, one method to improve the machinability of TiAl alloys is to add alloying elements to form β phase at high temperature. For example, β phase can be stabilized by alloying with β isomorphous elements (such as Nb, V and Ta) or β-eutectoid elements (such as Cr, Fe, Mn, Ni and W). More and more alloys based on β phase have been used in aerospace and automotive industries. The disordered β phase with bcc lattice structure provides a sufficient number of independent slip systems and is softer than d phase and γ phase, so β ​​phase stabilized TiAl alloys (such as TiAlNi alloys) can be hot forged under conditions close to conventional conditions with good machinability.

[0004] However, the β-phase stabilized TiAl alloy obtained by the above method in the prior art, while improving the machinability of the material, also sacrifices the high temperature performance of the material (compressive strength and creep resistance under high temperature conditions) to a certain extent. Therefore, how to obtain a TiAl alloy with compressive strength and creep resistance under high temperature conditions has become a technical problem to be solved in the art. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a titanium-aluminum-nickel high-temperature alloy. The present invention simultaneously adds trace elements such as C and Ce to the TiAl alloy and optimizes the element ratio, and at the same time combines process optimization to obtain a titanium-aluminum-nickel high-temperature alloy having excellent high-temperature compressive strength and creep resistance, as well as excellent corrosion resistance.

[0006] The specific technical scheme of the present invention is:

[0007] In a first aspect, the present invention provides a titanium-aluminum-nickel high-temperature alloy, which comprises the following chemical components, measured by mass percentage: A1=45-50%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4% and the remainder Ti.

[0008] The titanium aluminum nickel high temperature alloy of the present invention contains α phase, γ phase, β phase and a granular Ti3AlC phase with pinned dislocation; the volume fraction of the β phase is 5-18%. The titanium aluminum nickel high temperature alloy of the present invention has a layered structure; the interlayer distance range is 150-250nm).

[0009] In the titanium-aluminum-nickel high-temperature alloy of the present invention, Al and Ti are the main chemical components, and are doped with appropriate amounts of Ni, Mo, C and Ce. Specifically:

[0010] In the present invention, Ni and Ti can form a continuous solid solution with infinite solid solution, and a proper amount of Ni can inhibit the nucleation and growth of discontinuous precipitation phases in the alloy, thereby significantly improving the machinability of the alloy.

[0011] The present invention finds that adding an appropriate amount of C and Ce to the titanium-aluminum-nickel high-temperature alloy can appropriately reduce the proportion of the β phase, refine the interlayer spacing, and further induce the precipitation of Ti3AlC phase particles. The orientation relationship between Ti3AlC and γ-TiAl phase is (001) P / / (001) γ and

[010] P / /

[010] γ , which indicates that Ti3AlC pins dislocations and can inhibit the movement of dislocations, thereby greatly improving the compressive strength and creep resistance of the high-temperature alloy. Therefore, the improvement of the high-temperature performance (high-temperature compressive strength and creep resistance) of the titanium-aluminum-nickel high-temperature alloy of the present invention is due to the precipitation strengthening of Ti3AlC particles, the refinement of the lamellar structure, the reduction of the proportion of β phase, and the solid solution strengthening of interstitial carbon elements. However, the content of C and Ce needs to be controlled. If the content is too much, the machinability of the alloy will be significantly reduced.

[0012] In addition, in the present invention, the Mo element plays a high-temperature antioxidant role, which can refine the cast grain structure, inhibit grain boundary reaction and grain coarsening, and delay the precipitation of discontinuous precipitates during aging, thereby further improving the strength of the titanium-aluminum-nickel high-temperature alloy.

[0013] In summary, the titanium-aluminum-nickel high-temperature alloy of the present invention has both excellent processability and excellent high-temperature performance (compressive strength and creep resistance), as well as excellent electrical conductivity and corrosion resistance.

[0014] Preferably, the titanium-aluminum-nickel high-temperature alloy comprises the following chemical components by mass percentage: Al=46-49%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4%, Ti=42-52%.

[0015] Further preferably, the titanium-aluminum-nickel high-temperature alloy comprises the following chemical components in percentage by mass: Al=46.5_49%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4%, Ti=42-51.5%.

[0016] Most preferably, the titanium-aluminum-nickel high-temperature alloy comprises the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.5%, Ce=0.4% and Ti=44.1%.

[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned titanium-aluminum-nickel high-temperature alloy, comprising:

[0018] 1) Weigh each element and alloy according to the ratio.

[0019] 2) Add TiAl master alloy, Ni and Mo into a smelting device and increase the temperature.

[0020] 3) When the temperature rises to 1240-1260°C, add Ce wrapped in aluminum foil to the bottom of the molten alloy.

[0021] 4) When the temperature rises to 1270-1290°C, add aluminum foil package C to the bottom of the molten alloy.

[0022] Adding Ce and C in the form of aluminum foil wrapping can prevent Ce and C from oxidizing before reaching the bottom of the smelting device.

[0023] 5) Raise the temperature to 1350-1390°C and horizontally continuously cast the molten alloy into rods.

[0024] 6) Homogenize the rod to obtain the finished product.

[0025] Preferably, in 1), each element and alloy is pretreated to remove impurities.

[0026] Preferably, in 2), the smelting device is a medium frequency induction furnace; further preferably, the diameter of the cast rod is φ=18-22 mm.

[0027] Preferably, in 5), the casting speed of the horizontal continuous casting is 1.8-2.5 m / min.

[0028] The present invention finds that the billet drawing speed during the horizontal continuous casting process affects the metallographic structure and performance of the alloy. In addition, when the billet drawing speed is too low, the solidified billet shell of the cast billet will increase, the billet drawing resistance will increase, and it is easy to be firmly bonded; when the billet drawing speed is too high, the solidified billet shell of the cast billet will become thinner, and it is easy to leak and cause accidents.

[0029] Preferably, during the whole process, an inert gas is passed through the top furnace opening of the smelting device for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0030] Preferably, in 6), the homogenization is firstly performed by cooling the temperature from 1180-1220°C to 880-920°C at 3-5°C / min, and then cooling the temperature to room temperature at 4-10°C / min.

[0031] The present invention finds that the homogenization process will significantly affect the microstructure and various properties of the titanium-aluminum-nickel high-temperature alloy.

[0032] The present invention finds that the homogenization process affects the metallographic structure and performance of the alloy, so the size and amount of the precipitated phase can be controlled by controlling the homogenization process parameters. If the cooling rate is too fast, the precipitated phase will not precipitate in time and will not play the role of pinning the grain boundary; on the contrary, if the cooling rate is too slow, the precipitated phase will grow, which is not conducive to pinning the grain boundary and precipitation strengthening.

[0033] In a third aspect, the present invention provides the use of Ce and C in improving the high temperature compressive strength and / or high temperature creep resistance of titanium-aluminum-nickel high temperature alloys.

[0034] In a fourth aspect, the present invention provides the use of Ce and C in improving the electrical conductivity and / or corrosion resistance of titanium-aluminum-nickel high-temperature alloys.

[0035] In a fifth aspect, the present invention provides the use of Ce and C in reducing the proportion of β phase in titanium aluminum nickel high temperature alloys, reducing interlayer spacing, and inducing Ti3AlC phase precipitation.

[0036] Compared with the prior art, the beneficial effects of the present invention are:

[0037] The present invention simultaneously adds trace elements such as C and Ce to the TiAl alloy and optimizes the element ratio, while combining process optimization to obtain a titanium-aluminum-nickel high-temperature alloy having excellent high-temperature compressive strength and creep resistance as well as excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a TEM image of the dislocation structure of the titanium-aluminum-nickel high-temperature alloy in Example 1 of the present invention under a compression test (scale bar is 200 nm).

[0039] Figure 2 This is the SAED image of the titanium-aluminum-nickel high-temperature alloy under compression test in Example 1 of the present invention (the scale bar is 5 nm).

[0040] Figure 3 This is a SEM image of the titanium-aluminum-nickel high-temperature alloy Ti-48Al-4Ni-3Mo of Example 1 of the present invention (the scale bar is 10 nm). DETAILED DESCRIPTION

[0041] For ease of understanding, the technical solutions and implementation methods of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] The preparation methods, materials, structures or composition ratios not explicitly described in the following examples are all considered to be common technical features disclosed in the prior art. The materials, reagents, etc. used in the examples can be obtained from commercial sources unless otherwise specified.

[0043] Overall embodiment

[0044] Firstly, a titanium-aluminum-nickel high-temperature alloy includes the following chemical components by mass percentage: Al=45-50%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4% and the balance Ti.

[0045] Preferably, the titanium, aluminum, nickel high-temperature alloy comprises the following chemical compositions, calculated by mass percentage: Al=46-49%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4%, Ti=42-52%; further preferably, the titanium, aluminum, nickel high-temperature alloy comprises the following chemical compositions, calculated by mass percentage: A1=46.5-49%, Ni=2-4%, Mo≤3%, C≤0.5%, Ce≤0.4%, Ti=42-51.5%; most preferably, the titanium, aluminum, nickel high-temperature alloy comprises the following chemical compositions, calculated by mass percentage: A1=48%, Ni=4%, Mo=3%, C=0.5%, Ce=0.4% and Ti=44.1%.

[0046] The titanium aluminum nickel high temperature alloy of the present invention contains d phase, γ phase, β phase and a granular Ti3AlC phase with pinned dislocations; the volume fraction of the β phase is 5-18%. The titanium aluminum nickel high temperature alloy of the present invention has a layered structure; the interlayer spacing ranges from 150 to 250 nm.

[0047] A method for preparing the above-mentioned titanium-aluminum-nickel high-temperature alloy comprises:

[0048] 1) Weigh each element and alloy according to the ratio.

[0049] In some specific implementation cases, the individual elements and alloys are pre-treated to remove impurities.

[0050] 2) Add TiAl master alloy, Ni and Mo into a smelting device and raise the temperature to heating.

[0051] In some specific implementation cases, the smelting device is a medium frequency induction furnace. In some more specific implementation cases, the diameter of the medium frequency induction furnace is φ=18-22 mm.

[0052] 3) When the temperature rises to 1240-1260°C, add Ce wrapped in aluminum foil to the bottom of the molten alloy.

[0053] 4) When the temperature rises to 1270-1290°C, add aluminum foil package C to the bottom of the molten alloy.

[0054] 5) Raise the temperature to 1350-1390°C and horizontally continuously cast the molten alloy into rods.

[0055] In some specific implementation cases, the casting speed of horizontal continuous casting is 1.8-2.5 m / min.

[0056] 6) Homogenize the rod to obtain the finished product.

[0057] In some specific implementation cases, the homogenization is first performed by decreasing the temperature from 1180-1220° C. to 880-920° C. at 3-5° C. / min, and then decreasing the temperature to room temperature at 4-10° C. / min.

[0058] In some specific implementation cases, during the whole process, the top furnace opening of the smelting device is protected by inert gas, and the bottom is passed through hydrogen to isolate oxygen.

[0059] Specific Examples and Comparative Examples

[0060] Example 1

[0061] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.5%, Ce=0.4% and Ti=44.1%.

[0062] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0063] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0064] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0065] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0066] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0067] 5) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0068] 6) Transfer the rod to a muffle furnace for homogenization: first reduce the temperature from 1200°C to 900°C at 4°C / min, and then reduce the temperature to room temperature at 7°C / min to obtain the finished product.

[0069] Comparative Example 1 (Compared with Example 1, without C and Ce)

[0070] A titanium-aluminum-nickel high-temperature alloy has the following chemical composition by mass percentage: Al=48%, Ni=4%, Mo=3% and Ti=45%.

[0071] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0072] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0073] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0074] 3) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0075] 4) The rods are transferred to a muffle furnace for homogenization: first, the temperature is reduced from 1200°C to 900°C at 4°C / min, and then reduced to room temperature at 7°C / min to obtain the finished product.

[0076] Comparative Example 2 (Compared with Example 1, without C)

[0077] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, Ce=0.4% and Ti=44.6%.

[0078] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0079] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0080] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0081] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0082] 4) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0083] 5) The rods are transferred to a muffle furnace for homogenization: first, the temperature is reduced from 1200°C to 900°C at 4°C / min, and then reduced to room temperature at 7°C / min to obtain the finished product.

[0084] Comparative Example 3 (Compared with Example 1, without Ce)

[0085] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.5% and Ti=44.5%.

[0086] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0087] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0088] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0089] 3) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0090] 4) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0091] 5) The rods are transferred to a muffle furnace for homogenization: first, the temperature is reduced from 1200°C to 900°C at 4°C / min, and then reduced to room temperature at 7°C / min to obtain the finished product.

[0092] Comparative Example 4 (Compared with Example 1, the C and Ce contents are too high)

[0093] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.8%, Ce=0.6% and Ti=43.6%.

[0094] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0095] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0096] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0097] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0098] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0099] 5) The temperature was raised to 1370°C and the molten alloy was horizontally continuously cast into rods at a casting speed of 2.2 m / min. As a result, the horizontal continuous casting failed.

[0100] During the whole process, argon gas is passed through the top of the medium frequency induction furnace for protection, and hydrogen gas is passed through the bottom to isolate oxygen.

[0101] Comparative Example 5 (Different Homogenization Process)

[0102] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: A1=48%, Ni=4%, Mo=3%, C=0.5%, Ce=0.4% and Ti=44.1%.

[0103] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0104] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0105] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0106] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0107] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0108] 5) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0109] 6) The rods are transferred to a muffle furnace for homogenization: the temperature is reduced from 1200°C to room temperature at a rate of 10°C / min to obtain the finished product.

[0110] Comparative Example 6 (Different Homogenization Process)

[0111] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.5%, Ce=0.4% and Ti=44.1%.

[0112] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0113] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0114] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0115] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0116] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0117] 5) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0118] 6) The rods are transferred to a muffle furnace for homogenization: the temperature is reduced from 1200°C to room temperature at 2°C / min to obtain the finished product.

[0119] Example 2

[0120] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.2%, Ce=0.1% and Ti=43.5%.

[0121] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0122] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0123] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0124] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0125] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0126] 5) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0127] 6) Transfer the rod to a muffle furnace for homogenization: first reduce the temperature from 1200°C to 900°C at 4°C / min, and then reduce the temperature to room temperature at 7°C / min to obtain the finished product.

[0128] Example 3

[0129] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: Al=48%, Ni=4%, Mo=3%, C=0.3%, Ce=0.2% and Ti=43.7%.

[0130] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0131] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0132] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0133] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0134] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0135] 5) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0136] 6) Transfer the rod to a muffle furnace for homogenization: first reduce the temperature from 1200°C to 900°C at 4°C / min, and then reduce the temperature to room temperature at 7°C / min to obtain the finished product.

[0137] Example 4

[0138] A titanium-aluminum-nickel high-temperature alloy has the following chemical compositions by mass percentage: A1=48%, Ni=4%, Mo=3%, C=0.4%, Ce=0.3% and Ti=43.9%.

[0139] The preparation method of the titanium-aluminum-nickel high-temperature alloy comprises:

[0140] 1) Weigh each element and alloy according to the proportion and remove impurities.

[0141] 2) First, TiAl master alloy, Ni and Mo are added into a medium frequency induction furnace (φ=20 mm) and mixed evenly, and then the temperature is increased by using an increasing power, and the power increasing program is 0W-50W-100W-150W-200W-400W-600W.

[0142] 3) When the temperature is raised to 1250°C, add Ce wrapped in aluminum foil (the aluminum content is calculated based on the mass of the aluminum foil) to the bottom of the molten alloy.

[0143] 4) When the temperature is raised to 1280°C, add aluminum foil (the mass of the aluminum foil is calculated by wrapping C inside the aluminum package) to the bottom of the molten alloy.

[0144] 5) The temperature is raised to 1370°C, and the molten alloy is horizontally continuously cast into rods at a billet drawing speed of 2.2 m / min. During the above process, argon is passed through the top of the medium frequency induction furnace for protection, and hydrogen is passed through the bottom to isolate oxygen.

[0145] 6) Transfer the rod to a muffle furnace for homogenization: first reduce the temperature from 1200°C to 900°C at 4°C / min, and then reduce the temperature to room temperature at 7°C / min to obtain the finished product.

[0146] Performance Testing

[0147] The high temperature alloys prepared in the above embodiments and comparative examples were subjected to various performance tests:

[0148] (1) Microstructure: Field emission scanning electron microscopy (FE-SEM, FEI NOVANANOSEM 230) and transmission electron microscopy (TEM, JEOL 2100F) were used to observe the microstructure of the samples before and after deformation. The SEM samples were electropolished using 30 mL nitric acid and 70 mL methanol solution, and the TEM samples were prepared by double jet polishing at -30 °C and 20 V in an electrolyte solution containing 5% perchloric acid, 35% butanol, and 60% methanol (volume fraction).

[0149] (2) High temperature creep resistance test method: record the original length L0 of the sample, fix one end of the sample, stretch the other end of the sample at 850°C and 200 MPa until the sample breaks, record the length L1 of the sample at the moment of breakage, and calculate the creep elongation of the sample = (L1-L0) / L0*100%.

[0150] (3) The test method of salt spray test is: GB / T10125 Artificial atmosphere corrosion test salt spray test-neutral salt spray test.

[0151] The test results are shown in the following table:

[0152]

[0153]

[0154] By comparing the data in the above table, we can see that:

[0155] The volume proportion of the β phase and the interlamellar spacing in the high-temperature alloy material obtained in each embodiment are small, the high-temperature compressive strength and high-temperature creep resistance are good, and the corrosion resistance is also excellent.

[0156] Compared with Example 1, the alloy raw materials of Comparative Examples 1-3 contain no C and Ce, no C, and no Ce, respectively. The results show that the volume proportion of the β phase and the interlamellar spacing in the final alloy materials are larger, the high-temperature compressive strength and high-temperature creep resistance are poor, and the corrosion resistance is not as good as that of Example 1.

[0157] The C and Ce contents in the alloy raw material of Comparative Example 4 are too high, which makes it impossible to carry out horizontal continuous casting, and thus it is impossible to obtain a formed alloy material.

[0158] Compared with Example 1, the cooling rates of Comparative Examples 5-6 during the homogenization process were too fast and too slow, respectively, which resulted in a larger volume ratio of the β phase and the interlamellar spacing in the final alloy material, poor high-temperature compressive strength and high-temperature creep resistance, and the corrosion resistance was not as good as Example 1. However, compared with Comparative Examples 1-3, the performance is better.

[0159] Figure 1This is a TEM image of the dislocation structure of the titanium-aluminum-nickel high-temperature alloy under compression test in Example 1 of the present invention (scale bar is 200 nm). Figure 2 This is the SAED image of the titanium-aluminum-nickel high-temperature alloy in the compression test of Example 1 of the present invention (the scale bar is 5 nm). Through SAED analysis, the precipitate is Ti3AlC, and the orientation relationship between Ti3AlC and γ-TiAl phase can be determined to be (001) P / / (001) γ and

[010] P / /

[010] γ This indicates that Ti3AlC precipitates pinned dislocations and inhibited the movement of dislocations, thereby greatly improving the high-temperature compressive strength and creep resistance of the high-temperature alloy. Figure 3 This is a SEM image of the high-temperature alloy obtained in Example 1 of the present invention (the scale bar is 10 nm), from which the existence of various metallographic phases can be observed.

[0160] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a titanium-aluminum-nickel high-temperature alloy, characterized in that include: 1) Titanium-aluminum-nickel high-temperature alloy includes, by mass percentage: Al=45-50%, Ni=2-4%, 0<Mo≤3%, 0<C≤0.5%, 0<Ce≤0.4% and the balance Ti; weigh each element and alloy according to the proportion; 2) Add TiAl master alloy, Ni and Mo into the smelting device and increase the temperature; 3) Raise the temperature to 1240-1260°C and add Ce wrapped in aluminum foil to the bottom of the molten alloy; 4) Raise the temperature to 1270-1290℃ and add aluminum foil wrapped C to the bottom of the molten alloy; 5) Raise the temperature to 1350-1390°C and horizontally cast the molten alloy into rods; 6) Homogenize the rods: first reduce the temperature from 1180-1220℃ to 880-920℃ at 3-5℃ / min, and then reduce it to room temperature at 4-10℃ / min to obtain the finished product.

2. The preparation method according to claim 1, characterized in that: The titanium-aluminum-nickel high-temperature alloy contains a Ti3AlC phase with pinned dislocations.

3. The preparation method according to claim 1 or 2, characterized in that: The titanium-aluminum-nickel high-temperature alloy comprises the following chemical components by mass percentage: Al=46-49%, Ni=2-4%, 0<Mo≤3%, 0<C≤0.5%, 0<Ce≤0.4%, and Ti=43.5-52%.

4. The preparation method according to claim 3, characterized in that: Calculated by mass percentage, the titanium-aluminum-nickel high-temperature alloy includes the following chemical components: Al=46.5-49%, Ni=2-4%, 0<Mo≤3%, 0<C≤0.5%, 0<Ce≤0.4%, and Ti=43.5-51.5%.

5. The preparation method according to claim 4, characterized in that: Calculated by mass percentage, the titanium-aluminum-nickel high-temperature alloy includes the following chemical components: Al=48%, Ni=4%, Mo=3%, C=0.5%, Ce=0.4%, and Ti=44.1%.

6. The preparation method according to claim 1, characterized in that: 5), the casting speed of the horizontal continuous casting is 1.8-2.5 m / min.

7. The preparation method according to claim 1, characterized in that: 1), the single elements and alloys are pre-treated to remove impurities.

8. The preparation method according to claim 1, characterized in that: 2), the smelting device is a medium frequency induction furnace.

9. The preparation method according to claim 8, characterized in that: 5), the diameter of the medium frequency induction furnace is φ=18-22mm.

Citation Information

Patent Citations

  • Titanium-based powder metallurgy brake disc material and preparation method thereof

    CN103122426A

  • KR1018429220000B1